Lithium iron phosphate slurry dispersibility improving method and slurry preparation method
By detecting the resistivity and particle size distribution of lithium iron phosphate powder, different homogenization methods are used for powders of different dispersibility categories, which solves the problem of poor dispersion of lithium iron phosphate paste and improves the stability and accuracy of battery electrical performance testing.
Patent Information
- Application Number
- CN202411716597.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
AI Technical Summary
In the preparation of lithium iron phosphate live substance slurry, the dispersion of different lithium iron phosphate powders has been failed to effectively improve the dispersion of different lithium iron phosphate powders, resulting in the stability and accuracy of battery electrical performance testing.
By detecting the resistivity and particle size distribution of lithium iron phosphate powder, it is divided into different categories of dispersion, and different homogenization methods are used for different categories of powder to improve the dispersion effect of the slurry.
It improves the dispersion of the live substance slurry of the button battery, enhances the stability and accuracy of electrical performance testing, and reduces costs and improves testing efficiency.
Smart Images

Figure CN119549047A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery slurry, and particularly relates to a method for improving the dispersibility of lithium iron phosphate slurry and a method for preparing the slurry. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] With the rapid development of the lithium battery industry, reverse research on batteries has reached the level of positive and negative electrode materials. Lithium iron phosphate has become the most promising positive electrode material in the lithium-ion battery industry due to its advantages such as high safety, long cycle life, environmental friendliness and low cost. Among them, button batteries, whether used as finished lithium batteries or as a test verification before making batteries, are an effective method for evaluating the electrical performance of lithium iron phosphate materials. The differences in the preparation process of button batteries have a great impact on the electrical performance of subsequent batteries, especially the preparation process of the front-end pole piece. Therefore, the preparation of active material slurry, which has the greatest impact on the preparation of pole pieces, has begun to be valued by people.
[0004] The current mainstream lithium iron phosphate active material slurry is mainly composed of solvent, lithium iron phosphate powder, binder, and conductive agent. The solvent is divided into two systems: water system and oil system. After all the components are mixed and dispersed evenly by shearing, the active material slurry can be obtained. Specifically, for example, in patent CN117766673A, the binder is dissolved in the solvent, stirred for the first time, the conductive agent is added, stirred for the second time, and the conductive glue is obtained. The conductive glue is mixed with the negative electrode main material or the positive electrode main material, and stirred for the third time to obtain the negative electrode slurry or the positive electrode slurry, wherein the rotation speed and duration of the three stirrings and the solid content of the slurry are controlled. However, these mainstream methods for preparing active material slurries for button battery pole pieces have obvious defects. They do not pay attention to the key factors that affect the capacity of the pole piece, that is, different lithium iron phosphates have different dispersibilities in the slurry, and the dispersion effects of the obtained slurries are all different.
[0005] The different dispersibility of lithium iron phosphate means that even if the slurry is adjusted to the same solid content or the same viscosity, it is impossible to ensure that different slurries are at the same or equivalent dispersion level. Slurries with different degrees of dispersion uniformity have a huge difference in capacity, which will seriously affect the judgment and comparison of the electrical performance of different lithium iron phosphate powder materials themselves.
[0006] At the same time, there is no obvious difference between the easy-to-disperse lithium iron phosphate powder using a simple and general dispersion method and a method that enhances the dispersion effect. The cost of using the enhanced slurry dispersion method to prepare lithium iron phosphate active material slurry is high and the preparation efficiency is low.
[0007] Therefore, finding an effective method to improve the dispersion of different lithium iron phosphate slurries has become a key task in improving the stability and accuracy of button battery electrical performance testing. Summary of the invention
[0008] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for improving the dispersibility of lithium iron phosphate slurry and a method for preparing the slurry.
[0009] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0010] In a first aspect, the present invention provides a method for improving the dispersibility of lithium iron phosphate slurry, comprising the following steps: detecting the resistivity and particle size distribution of the lithium iron phosphate powder to be tested, and classifying it as Class A when the resistivity is less than a set value, and classifying it as Class B when the resistivity is greater than the set value;
[0011] If the percentage of particles with a particle size of less than 0.1 μm to the total number of particles is greater than 15%, and the percentage of particles with a particle size of 0.1 to 0.15 μm to the total number of particles is greater than 30%, they are classified as Class C, and if they do not meet the requirements, they are classified as Class D;
[0012] The lithium iron phosphate powder that meets both A and C has poor dispersibility;
[0013] The lithium iron phosphate powder that satisfies A and D, or / and B and C at the same time has moderate dispersibility;
[0014] The lithium iron phosphate powder that meets both B and D is excellent in dispersibility;
[0015] Different homogenization methods are applied to lithium iron phosphate powders with different dispersities.
[0016] In an ideal lithium iron phosphate battery active material slurry, the conductive agent and the binder are wrapped around the outside of each lithium iron phosphate particle in the form of a gel-like conductive network. The conductive agent and the binder in the slurry cannot be evenly wrapped around the lithium iron phosphate particles to form a network structure, too much conductive agent aggregates, and lithium iron phosphate particles aggregate, which are all manifestations of uneven dispersion of the slurry, that is, poor dispersion. The reasons for these phenomena are largely related to the carbon coating effect and particle size distribution of the corresponding lithium iron phosphate material itself. In order to improve conductivity, the lithium iron phosphate materials on the market have a carbon coating layer on the surface. The carbon coating layer is basically amorphous carbon, with many pores on the surface and inside, and there are some active groups on the surface of the carbon layer. These factors directly affect the solid-liquid specific surface energy between the particles and the slurry. The better the coating effect of the carbon coating layer and the more uniform the coating, the higher the polar component in the surface energy component, which will cause some of the above-mentioned slurry states to appear. During the processing of lithium iron phosphate, the particle size distribution of the finished lithium iron phosphate is different due to the differences in the preparation process and the precursor raw materials. The particles with smaller particle sizes in the overall distribution are called micropowders or fine powders. These small particles are prone to adsorption and agglomeration, and even affect the dispersion effect of other components in the slurry, which directly causes the appearance of some of the above-mentioned slurry states.
[0017] The present invention tests two key physical and chemical parameters, namely, the particle size distribution ratio and powder resistance of lithium iron phosphate materials, and specifically formulates a slurry dispersion method suitable for different lithium iron phosphates, thereby improving the dispersion effect of the electrically active material slurry made of lithium iron phosphate materials with different dispersivities. The powder resistance test is used to judge the dispersibility of lithium iron phosphate materials. The principle is that the better the carbon coating effect of the lithium iron phosphate material, the better its conductivity, that is, the lower the powder resistivity. This judgment method can be used to make a qualitative analysis of the carbon coating effect that is not easy to characterize, and then judge the dispersibility of the lithium iron phosphate material. Particles with a diameter less than 0.1μm and particles with a diameter in the range of 0.1-0.15μm belong to the fine powder level in the entire lithium iron phosphate material particle distribution. The particles are counted using SEM pictures taken at 10,000 times the magnification. When the number of particles less than 0.1μm accounts for more than 15% of the total number of particles and the number of particles with a diameter in the range of 0.1-0.15μm accounts for more than 30% of the total number of particles, the fine powder agglomeration effect has a significant impact on the slurry dispersion, and the slurry viscosity rises sharply. Therefore, this method can be used to make a qualitative analysis of the dispersibility of the lithium iron phosphate material.
[0018] In a second aspect, the present invention provides a method for preparing lithium iron phosphate slurry, comprising the following steps: detecting the resistivity and particle size distribution of the lithium iron phosphate powder to be tested, and classifying it as Class A when the resistivity is less than a set value, and classifying it as Class B when the resistivity is greater than the set value;
[0019] If the percentage of particles with a particle size of less than 0.1 μm to the total number of particles is greater than 15%, and the percentage of particles with a particle size of 0.1 to 0.15 μm to the total number of particles is greater than 30%, they are classified as Class C, and if they do not meet the requirements, they are classified as Class D;
[0020] The lithium iron phosphate powder that meets both A and C has poor dispersibility;
[0021] The lithium iron phosphate powder that satisfies A and D, or / and B and C at the same time has moderate dispersibility;
[0022] The lithium iron phosphate powder that meets both B and D is excellent in dispersibility;
[0023] Different homogenization methods are applied to lithium iron phosphate powders with different dispersities.
[0024] In some embodiments, during homogenization, the proportions of lithium iron phosphate with poor dispersibility, moderate dispersibility, and excellent dispersibility in the slurry solids decrease in sequence; and the proportion of the conductive agent in the slurry solids increases in sequence.
[0025] Adding too much conductive agent can easily cause conductive agent aggregation in the slurry, increasing impedance. Adding less conductive agent will result in larger electrode resistance, affecting the normal performance of the electrical properties of the lithium iron phosphate material. At the same time, the amount of conductive agent added is proportional to the viscosity of the slurry. The more conductive agent, the thicker the slurry and the harder it is to disperse. Lithium iron phosphate materials with better dispersibility have poor carbon coating effects and less fine powder, which means poor conductivity and lower capacity. Therefore, the electrical performance can be optimized by increasing the amount of conductive agent added to the slurry. Lithium iron phosphate materials with poor dispersibility have better carbon coating effects and more fine powder, which means better capacity but poor slurry uniformity and dispersion. Therefore, the dispersion effect of the slurry can be improved by reducing the amount of conductive agent added.
[0026] Preferably, the conductive agent in the slurry is selected from SP, carbon nanotubes CNT, carbon nanofibers VGCF, Ketjen black ECP, reduced graphene oxide rGO, acetylene black or Carbon ECP;
[0027] The binder is selected from polyvinylidene fluoride PVDF, polyacrylic acid PAA, polymethyl methacrylate PMMA or polytetrafluoroethylene PTFE.
[0028] The main component of SP conductive agent is missile carbon black, which is usually prepared by furnace method (MMM method). Its primary particle diameter is about 40nm, and it agglomerates into primary aggregates of 150-200nm.
[0029] Preferably, during homogenization, the mass ratio of the poorly dispersible lithium iron phosphate, the conductive agent and the binder in the slurry is 91-92:3-4:5.
[0030] More preferably, the solid content of the lithium iron phosphate slurry with poor dispersibility is 30% to 35%.
[0031] More preferably, when homogenizing, the binder is first mixed with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and all the lithium iron phosphate, conductive agent and half of the glue solution are mixed and degassed. The degassed process is 700 to 800 rpm for 30 to 60 s, 1900 to 2000 rpm for 12 to 15 min, and the degassed process is repeated 2 to 4 times. The other half of the glue solution is added for secondary degassed, and the degassed process is the same as above. After the degassed process is completed, the solid content of the slurry is adjusted to the set value.
[0032] For the preparation of lithium iron phosphate slurry with poor dispersibility, adding binder in two steps can appropriately slow down the viscosity climb of the slurry and reduce the shear stress and dispersion time required to achieve uniform dispersion during the slurry dispersion process. It is an effective method to improve the slurry dispersion effect.
[0033] Preferably, during homogenization, the mass ratio of lithium iron phosphate with moderate dispersibility, the conductive agent and the binder in the slurry is 90-91:4-5:5.
[0034] More preferably, the solid content of the lithium iron phosphate slurry with moderate dispersibility is 35% to 40%.
[0035] More preferably, during homogenization, the binder is first mixed with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and all the lithium iron phosphate, conductive agent and glue solution are mixed and degassed. The degashing process is 700 to 800 rpm for 30 to 60 s, 1700 to 1900 rpm for 12 to 15 min, and the degashing process is repeated 2 to 4 times; after the degashing is completed, the solid content of the slurry is adjusted to the set value.
[0036] Preferably, during homogenization, the mass ratio of lithium iron phosphate with excellent dispersibility, the conductive agent and the binder in the slurry is 89-90:5-6:5.
[0037] More preferably, the solid content of the lithium iron phosphate slurry with excellent dispersibility is 40% to 45%.
[0038] More preferably, during homogenization, the binder is first mixed with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and all the lithium iron phosphate, conductive agent and glue solution are mixed and degassed. The degashing process is 700 to 800 rpm for 30 to 60 s, 1700 to 1900 rpm for 12 to 15 min, and the degashing process is repeated 2 to 4 times; after the degashing is completed, the solid content of the slurry is adjusted to the set value.
[0039] Still more preferably, the solid content of the glue solution is 3%-6%, preferably 5%.
[0040] For lithium iron phosphate materials that are easy to disperse, appropriately reducing the amount of NMP added and the degassing and dispersion speed to increase the solid content of the slurry can effectively control the cost and the stability of the active material surface density during electrode coating without affecting the slurry state and subsequent electrical performance tests. For lithium iron phosphate materials that are difficult to disperse, increasing the degassing and dispersion speed and the amount of NMP added and reducing the solid content of the slurry can reduce the damage to the conductive network structure wrapped by the binder and conductive agent and the agglomeration of the conductive agent and lithium iron phosphate, further improving the slurry dispersion effect.
[0041] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0042] In view of different lithium iron phosphate materials with different dispersivities, in order to improve the dispersion effect of their button battery (hereinafter referred to as button battery) active material slurry, and improve the stability and accuracy of the button battery electrical performance test, the present invention provides a button battery slurry dispersion improvement method and a specific slurry preparation process. The carbon coating uniformity and micro-powder situation of different lithium iron phosphate materials are distinguished by the two key physical and chemical parameters of particle size distribution ratio and powder resistance, and then the dispersibility of the sample to be tested is judged, and then the slurry preparation method corresponding to the lithium iron phosphate material with different dispersivities is used to prepare the slurry, and the button battery slurry with uniform dispersion of each component is obtained. The pole piece after the slurry is coated with the roller is observed under SEM without obvious SP or lithium iron phosphate particle agglomeration, the overall chromaticity of the SEM test area is uniform, and there is no block-distributed black shadow or white highlight area. The electrical performance test results after the button battery are made show that the parallel samples have the advantages of high parallelism and high accuracy between the comparison samples. At the same time, the targeted customization of the slurry can greatly save costs and improve the test efficiency without affecting the test level. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0044] Figure 1 is a SEM image of a rolled electrode sheet made from the slurry of Example 1;
[0045] Figure 2 is a SEM image of the rolled electrode sheet made from the slurry of Example 2;
[0046] Figure 3 is a SEM image of a rolled electrode sheet made from the slurry of Example 3;
[0047] Figure 4 is a SEM image of a rolled electrode sheet made from the slurry of Example 4;
[0048] Figure 5This is a SEM image of the rolled electrode sheet made from the slurry in Comparative Example 1;
[0049] Figure 6 This is the SEM image of the rolled electrode sheet made from the slurry in Comparative Example 2;
[0050] Figure 7 This is a SEM image of the rolled electrode sheet made from the slurry in Comparative Example 3;
[0051] Figure 8 This is the SEM image of the rolled electrode made from the slurry of Example 4. DETAILED DESCRIPTION
[0052] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0053] The present invention will be further described below in conjunction with the embodiments.
[0054] Example 1
[0055] 1. Take a lithium iron phosphate sample with a powder resistance test value of 13.1Ω·cm, a particle size of less than 0.1μm accounting for 23.86% of the total number of particles, and a particle size of 0.1-0.15μm accounting for 35.98% of the total number of particles. Use a four-probe powder resistivity tester to test the lithium iron phosphate sample to be tested. Set the pressure as the control target, the target pressure is 20000N, and the pressure holding time is 30s. The resistivity test results show that the sample powder resistance is less than 15Ω·cm, that is, the lithium iron phosphate sample is classified as Class A;
[0056] 2. The lithium iron phosphate sample was tested using a scanning electron microscope, with the acceleration voltage set to 10KV, the electron beam spot diameter to 7nm, the lens working distance to 10mm, and the magnification to 10,000 times. The particle size distribution of the SEM images taken was counted, and the number of all particles in the image and the corresponding particle size were counted. The statistical results confirmed that the percentage of particles with a particle size less than 0.1μm in the total number of particles was greater than 15%, and the percentage of particles with a particle size in the range of 0.1 to 0.15μm in the total number of particles was greater than 30%, that is, the lithium iron phosphate material was classified as Class C;
[0057] 3. The lithium iron phosphate material that meets both Class A and Class C conditions can be judged as a lithium iron phosphate material with poor dispersibility. When homogenizing, the mass ratio of lithium iron phosphate, SP, and PVDF components is controlled to be 91:4:5. The amount of NMP added to the slurry should be able to maintain the overall solid content of the slurry at 33%. First, PVDF and an appropriate amount of NMP are made into a 5% solid content glue solution, and then all the lithium iron phosphate, SP and half of the PVDF glue solution required for preparing the slurry are added to the degassing tank, and after weighing, they are placed in a degassing machine for degassing and dispersion. The degassing process is 800rpm for 60s and 2000rpm for 15min. After the process is repeated 3 times, the other half of the PVDF glue solution is added, and after weighing, it is placed in a degassing machine for secondary degassing and dispersion. The degassing process is the same as above, and the process is repeated 3 times. After each degassing, an appropriate amount of NMP is added according to the slurry state. Finally, the solid content is adjusted to the target value to obtain a uniformly dispersed buckle active material slurry.
[0058] Example 2
[0059] 1. Take a lithium iron phosphate sample with a powder resistance test value of 24.6Ω·cm, a particle size of less than 0.1μm accounting for 4.17% of the total number of particles, and a particle size of 0.1-0.15μm accounting for 21.30% of the total number of particles. Use a four-probe powder resistivity tester to test the lithium iron phosphate sample to be tested. Set the pressure as the control target, the target pressure is 20000N, and the pressure holding time is 30s. The resistivity test results show that the sample powder resistance is greater than 15Ω·cm, that is, the lithium iron phosphate sample is classified as Class B;
[0060] 2. The lithium iron phosphate sample was tested using a scanning electron microscope, with the acceleration voltage set to 10KV, the electron beam spot diameter to 7nm, the lens working distance to 10mm, and the magnification to 10,000 times. The particle size distribution of the SEM images taken was counted, and the number of all particles on the images and the corresponding particle sizes were counted. The statistical results confirmed that the percentage of particles with a particle size of less than 0.1μm in the total number of particles was less than 15%, and the percentage of particles with a particle size in the range of 0.1 to 0.15μm in the total number of particles was less than 30%, that is, the lithium iron phosphate material was classified as Class D;
[0061] 3. The lithium iron phosphate material that meets both Class B and Class D conditions can be judged as a lithium iron phosphate material with excellent dispersibility. When slurrying, the distribution ratio of lithium iron phosphate, SP, and PVDF is controlled to be 89:6:5. The amount of NMP added to the slurry should be able to maintain the overall solid content of the slurry at 42%. First, PVDF and an appropriate amount of NMP are made into a 5% solid content glue solution, and then all the lithium iron phosphate, SP and PVDF glue solutions required for preparing the slurry are added to the degassing tank. After weighing, they are placed in a degassing machine for degassing and dispersion. The degassing process is 650rpm for 60s and 1500rpm for 15min. The process is repeated 3 times. After each degassing, an appropriate amount of NMP is added according to the slurry state. Finally, the solid content is adjusted to the target value to obtain a uniformly dispersed buckle active material slurry.
[0062] Example 3
[0063] 1. Take a lithium iron phosphate sample with a powder resistance test value of 26.5Ω·cm, a particle size of less than 0.1μm accounting for 17.93% of the total number of particles, and a particle size of 0.1-0.15μm accounting for 35.48% of the total number of particles. Use a four-probe powder resistivity tester to test the lithium iron phosphate sample to be tested. Set the pressure as the control target, the target pressure is 20000N, and the pressure holding time is 30s. The resistivity test results show that the sample powder resistance is greater than 15Ω·cm, that is, the lithium iron phosphate sample is classified as Class B;
[0064] Step 2 is consistent with step 2 in <Example 1>;
[0065] 3. The lithium iron phosphate material that meets both Class B and Class C conditions can be judged as a lithium iron phosphate material with moderate dispersibility. When homogenizing, the distribution ratio of lithium iron phosphate, SP, and PVDF is controlled to be 90:5:5. The amount of NMP added to the slurry should be able to maintain the overall solid content of the slurry at 37%. First, PVDF and an appropriate amount of NMP are made into a 5% solid content glue solution, and then all the lithium iron phosphate, SP and PVDF glue solutions required for preparing the slurry are added to the degassing tank. After weighing, they are placed in a degassing machine for degassing and dispersion. The degassing process is 700rpm for 60s and 1800rpm for 15min. The process is repeated 3 times. After each degassing, an appropriate amount of NMP is added according to the slurry state. Finally, the solid content is adjusted to the target value to obtain a uniformly dispersed buckle active material slurry.
[0066] Example 4
[0067] 1. Take a lithium iron phosphate sample with a powder resistance test value of 8.9Ω·cm, a particle size of less than 0.1μm accounting for 13.77% of the total number of particles, and a particle size of 0.1-0.15μm accounting for 25.44% of the total number of particles. Use a four-probe powder resistivity tester to test the lithium iron phosphate sample to be tested. Set the pressure as the control target, the target pressure is 20000N, and the pressure holding time is 30s. The resistivity test results show that the sample powder resistance is greater than 15Ω·cm, that is, the lithium iron phosphate sample is classified as Class A;
[0068] Step 2 is consistent with step 2 in <Example 2>;
[0069] 3. The difference between step 3 and step 3 in <Example 3> is that the lithium iron phosphate material that meets both Class A and Class D conditions can be judged as a lithium iron phosphate material with moderate dispersibility, and the slurry preparation process is the same as that in Example 3.
[0070] Comparative Example 1
[0071] Take the same lithium iron phosphate as in <Example 1>, and control the distribution ratio of lithium iron phosphate, SP, and PVDF to 90:5:5 during homogenization. The amount of NMP added to the slurry should be able to maintain the overall solid content of the slurry at 42%. First, PVDF and an appropriate amount of NMP are prepared into a 5% solid content glue solution, and then all the lithium iron phosphate, SP and PVDF glue solutions required for preparing the slurry are added to the degassing tank. After weighing, they are placed in a degassing machine for degassing and dispersion. The degassing process is 650rpm for 60s and 1500rpm for 15min. The process is repeated 3 times. After each degassing, an appropriate amount of NMP is added according to the slurry state. Finally, the solid content is adjusted to the target value to obtain a buckle active material slurry.
[0072] Comparative Example 2
[0073] The difference from <Comparative Example 1> is that the lithium iron phosphate used is the same as that in <Example 2>.
[0074] Comparative Example 3
[0075] The difference from <Comparative Example 1> is that the lithium iron phosphate used is the same as that in <Example 3>.
[0076] Comparative Example 4
[0077] The difference from <Comparative Example 1> is that the lithium iron phosphate used is the same as that in <Example 4>.
[0078] Depend on Figures 1 to 8It can be seen that the pole pieces prepared in Examples 1-4 after slurry coating and roller pressing have no obvious SP or lithium iron phosphate particle agglomeration when observed under SEM, and the overall chromaticity of the SEM test area is uniform, without block-distributed black shadows or white highlight areas; and the pole pieces prepared in Comparative Examples 1-4, except for the easy-to-disperse Comparative Example 2, after slurry coating and roller pressing, all have varying degrees of SP or lithium iron phosphate particle agglomeration, accompanied by block-distributed black shadows and white highlight areas.
[0079] Preparation of lithium iron phosphate button electrode sheet: Stir the active material slurry prepared in Examples 1-4 and Comparative Examples 1-4 evenly, and apply the slurry evenly on aluminum foil on a coating machine to make a pole sheet, with a coating thickness of 200 μm. Put the coated pole sheet into a vacuum drying oven at a temperature of 105°C for 4 hours, take out the pole sheet and roll it on a roller press for use.
[0080] Preparation of button cells: The prepared electrode pieces were made into discs of appropriate size and placed in a vacuum drying oven at 105°C for 2 hours. The button cells were assembled in a glove box under an argon atmosphere. The electrolyte was 1M LiPF6+EC:DEC:DMC=1:1:1 (volume ratio), and the metal lithium sheet was the counter electrode. The capacity test was carried out on an American Arbin BT2000 battery tester at a test temperature of 25°C, a charge and discharge voltage range of 2 to 3.75V, and a charge and discharge rate of 0.1C and 1C, respectively.
[0081] The test method for the slurry conductivity is: use the Skit C6 slurry resistance meter of Kawahara Technology to test, connect the power of the equipment, turn on the equipment switch, wait for the instrument to start, put the standard solution into the electrode cup, input the electrode calibration solution 84μS / cm, wait for the system to automatically calibrate and calculate the electrode constant, and save the calibration data. After waiting for the test group to be entered, select the continuous mode, add the slurry to be tested to the three electrode cups respectively, and start the test in turn. The average value of the three slurry conductivities is the actual measured conductivity of the slurry. Pay attention to placing them from left to right in the order of high-medium-low, and try to keep the slurry liquid level in the three electrode cups level. Note that the slurry needs to cover the test electrode in the electrode cup;
[0082] The test method for slurry viscosity is: GB / T 10247-2008 "Viscosity Measurement Method" 4.0 Rotation Method;
[0083] The test method for the electrode resistivity is as follows: use the ACCFILM electrode test system of Kawahara Technology, open the ACCFILM test software, enter the group name, target pressure 10MPa, holding time 10s, boost speed 1MPa / s, and buck speed 1MPa / s in the "data display interface", select the single-point mode, cut three 5cm*5cm parallel samples of each electrode, place them on the sample table to be tested in turn, click Start Sample to obtain three test values, and the test result is the average of the three parallel samples.
[0084] Table 1 Comparison of physical and chemical properties of slurries and prepared electrodes of Examples 1-4 and Comparative Examples 1-4
[0085]
[0086] It can be seen from Table 1 that the slurry conductivity trends of Examples 1-4 are consistent with the opposite trends of the powder resistance of their respective lithium iron phosphate materials, and at the same time, they are maintained at a relatively uniform level compared with the comparative examples. The slurry viscosity has reached the same level through different slurrying processes, and the electrode sheet resistivity trend is consistent with the high and low trends of the powder resistance of their respective lithium iron phosphate materials, and at the same time, it is maintained at a relatively low level compared with the comparative examples. Although the lithium iron phosphate used in Comparative Example 1 has a low powder resistance (≤15Ω), the slurry resistivity is the lowest among all comparative examples, the slurry viscosity is the highest, and the electrode sheet resistivity is the largest, which confirms the influence of the dispersion of lithium iron phosphate on the homogenization effect and the prepared electrode sheet. At the same time, Comparative Example 2 and Example 2 use lithium iron phosphate powder raw materials with good dispersion, so the physical and chemical parameters of the slurries and the prepared electrode sheets of the two are not much different.
[0087] Table 2 Electrical properties of lithium iron phosphate prepared in the examples and comparative examples
[0088]
[0089] It can be seen from Table 2 that the buckle batteries made from the four lithium iron phosphate samples in Examples 1-4 are in line with the theoretical capacity trend. The lithium iron phosphate with low powder resistance and more fine powder in Example 1 has a higher capacity, the lithium iron phosphate with high powder resistance and less fine powder in Example 2 has a lower capacity, and Examples 3 and 4 have moderate capacity. Among the comparative examples, except for the lithium iron phosphate with better dispersibility used in Example 2, the capacity performance has no obvious effect. The capacity performance of the buckle batteries in the other comparative examples is reduced to varying degrees due to the influence of the dispersion degree of the slurry. Among them, Comparative Example 1 uses lithium iron phosphate with poor dispersibility, so the buckle battery capacity performance is extremely low, which leads to a misjudgment of the actual capacity performance of the lithium iron phosphate.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the dispersibility of lithium iron phosphate slurry, characterized in that: The steps include: testing the resistivity and particle size distribution of the lithium iron phosphate powder to be tested, and classifying it as Class A when the resistivity is less than a set value, and classifying it as Class B when the resistivity is greater than the set value; If the percentage of particles with a particle size of less than 0.1 μm to the total number of particles is greater than 15%, and the percentage of particles with a particle size of 0.1 to 0.15 μm to the total number of particles is greater than 30%, they are classified as Class C, and if they do not meet the requirements, they are classified as Class D; The lithium iron phosphate powder that meets both A and C has poor dispersibility; The lithium iron phosphate powder that satisfies A and D, or / and B and C at the same time has moderate dispersibility; The lithium iron phosphate powder that meets both B and D is excellent in dispersibility; Different homogenization methods are applied to lithium iron phosphate powders with different dispersities.
2. A method for preparing lithium iron phosphate slurry, characterized in that: The steps include: testing the resistivity and particle size distribution of the lithium iron phosphate powder to be tested, and classifying it as Class A when the resistivity is less than a set value, and classifying it as Class B when the resistivity is greater than the set value; If the percentage of particles with a particle size of less than 0.1 μm to the total number of particles is greater than 15%, and the percentage of particles with a particle size of 0.1 to 0.15 μm to the total number of particles is greater than 30%, they are classified as Class C, and if they do not meet the requirements, they are classified as Class D; The lithium iron phosphate powder that meets both A and C has poor dispersibility; The lithium iron phosphate powder that satisfies A and D, or / and B and C at the same time has moderate dispersibility; The lithium iron phosphate powder that meets both B and D is excellent in dispersibility; Different homogenization methods are applied to lithium iron phosphate powders with different dispersities.
3. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 1 or the method for preparing lithium iron phosphate slurry according to claim 2, characterized in that: During homogenization, the proportion of lithium iron phosphate with poor dispersibility, moderate dispersibility and excellent dispersibility in the slurry solid content decreases in turn; the proportion of conductive agent in the slurry solid content increases in turn.
4. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 3 or the method for preparing lithium iron phosphate slurry according to claim 3, characterized in that: The conductive agent in the slurry is selected from SP, carbon nanotubes CNT, carbon nanofibers VGCF, Ketjen black ECP, reduced graphene oxide rGO, acetylene black or Carbon ECP; The binder is selected from polyvinylidene fluoride PVDF, polyacrylic acid PAA, polymethyl methacrylate PMMA or polytetrafluoroethylene PTFE.
5. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 3 or the method for preparing lithium iron phosphate slurry according to claim 3, characterized in that: During homogenization, the mass ratio of poorly dispersed lithium iron phosphate, conductive agent and binder in the slurry is 91-92:3-4:5; Preferably, the solid content of the poorly dispersible lithium iron phosphate slurry is 30% to 35%; Preferably, when homogenizing, the binder is first mixed with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and all the lithium iron phosphate, conductive agent and half of the glue solution are mixed and degassed. The degassed process is 700 to 800 rpm for 30 to 60 s, 1900 to 2000 rpm for 12 to 15 min, and the degassed process is repeated 2 to 4 times. The other half of the glue solution is added for secondary degassed, and the degassed process is the same as above. After the degassed process is completed, the solid content of the slurry is adjusted to the set value.
6. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 3 or the method for preparing lithium iron phosphate slurry according to claim 3, characterized in that: When homogenizing, the mass ratio of lithium iron phosphate, conductive agent and binder with moderate dispersibility in the slurry is 90-91:4-5:5; Preferably, the solid content of the lithium iron phosphate slurry with moderate dispersibility is 35% to 40%.
7. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 6 or the method for preparing lithium iron phosphate slurry according to claim 6, characterized in that: When homogenizing, first mix the binder with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and mix all the lithium iron phosphate, conductive agent and glue solution for degassing. The degassing process is 700 to 800 rpm for 30 to 60 seconds, 1700 to 1900 rpm for 12 to 15 minutes, and the degassing process is repeated 2 to 4 times; after degassing, adjust the solid content of the slurry to the set value.
8. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 3 or the method for preparing lithium iron phosphate slurry according to claim 3, characterized in that: During homogenization, the mass ratio of lithium iron phosphate, the conductive agent and the binder with excellent dispersibility in the slurry is 89 to 90:5 to 6:
5.
9. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 8 or the method for preparing lithium iron phosphate slurry according to claim 9, characterized in that: The solid content of lithium iron phosphate slurry with excellent dispersibility is 40% to 45%.
10. The method for improving the dispersibility of lithium iron phosphate slurry according to claim 9 or the method for preparing lithium iron phosphate slurry according to claim 9, characterized in that: When homogenizing, first mix the binder with N-methyl-2-pyrrolidone to prepare a glue solution with a solid content of 3 to 10%, and mix all the lithium iron phosphate, conductive agent and glue solution for degassing. The degassing process is 700 to 800 rpm for 30 to 60 seconds, 1700 to 1900 rpm for 12 to 15 minutes, and the degassing process is repeated 2 to 4 times; after degassing, adjust the solid content of the slurry to the set value.